2019
DOI: 10.3389/fphys.2019.00871
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Irisin and Myostatin as Markers of Muscle Strength and Physical Condition in Elderly Subjects

Abstract: Background and objective Aging is a physiological process known to produce changes in body composition, affecting the musculature and leading to decreased muscle strength. Muscle in response to exercise acts as an endocrine organ, producing and releasing myokines such as irisin and myostatin that modulate muscular growth. Here, we aimed to evaluate the effects of low intensity resistance exercise, with or without protein supplementation, on body composition, anthropometric parameters and circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 64 publications
0
32
0
1
Order By: Relevance
“…Although a number of novel research studies have been focused on the relationship between serum myostatin and muscle mass and function, and thus, its potential as a biomarker, the results seem unclear. Most studies indicate that a higher circulating myostatin concentration can be found in patients with higher muscle mass [ 79 , 80 , 81 , 82 , 83 , 84 , 85 ], but a few research studies resulted in finding such an association only in men [ 86 , 87 ], and some did not show any correlation with muscle mass parameters at all [ 88 , 89 , 90 , 91 ]. A study on healthy, obese and metabolically unhealthy participants found a contradictory, significantly negative correlation between muscle mass and serum myostatin, suggesting a major influence of metabolic syndrome on circulating myostatin level [ 92 ].…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a number of novel research studies have been focused on the relationship between serum myostatin and muscle mass and function, and thus, its potential as a biomarker, the results seem unclear. Most studies indicate that a higher circulating myostatin concentration can be found in patients with higher muscle mass [ 79 , 80 , 81 , 82 , 83 , 84 , 85 ], but a few research studies resulted in finding such an association only in men [ 86 , 87 ], and some did not show any correlation with muscle mass parameters at all [ 88 , 89 , 90 , 91 ]. A study on healthy, obese and metabolically unhealthy participants found a contradictory, significantly negative correlation between muscle mass and serum myostatin, suggesting a major influence of metabolic syndrome on circulating myostatin level [ 92 ].…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%
“…Similarly, contradictory findings have been made regarding the relationship between serum myostatin and muscle function. Some studies found increased circulating myostatin concentrations in patients with better muscle function or physical performance [ 80 , 81 , 83 , 84 , 87 ], and several indicated such a relationship to be more apparent in the male population [ 85 , 93 ], while others did not show any clear correlation between those parameters [ 82 , 88 , 89 , 92 , 94 ].…”
Section: Myostatin and Muscle Wastingmentioning
confidence: 99%
See 1 more Smart Citation
“…They both play a significant role in bone metabolism as factors influencing bone microstructure and mechanical properties [79]. Irisin plays a crucial role in enhancing bone remodelling and increasing cortical bone mass in experimental animals, which ultimately increases bone strength [23,80]. In contrast, myostatin exerts negative effects on bone mass through osteoclast activation, which leads to increased bone remodeling, where bone resorption outpaces bone formation [81].…”
Section: Discussionmentioning
confidence: 99%
“…Kadar irisin berkorelasi secara positif dengan massa dan kekuatan otot. 18 Terdapat beberapa penjelasan tentang efek protektif irisin terhadap otot rangka untuk mencegah terjadinya sarkopenia. Hal ini dihubungkan dengan beberapa faktor seperti inflamasi kronis, status nutrisi, keadaan uremia, atau resistensi insulin.…”
Section: Diskusiunclassified